Tectonic settings of regional metamorphism. A discussion. - Oxburgh, E; Yardley, B; England, P (Royal Society, London, 1987)
The proceedings of a discussion meeting held in London in 1986, in association with IGCP Project 235 on 'Metamorphism and Geodynamics'. The 13 papers discuss theory and observation of orogenic processes, and range from the regional distribution of metamorphic rocks (Canada, New Zealand, Europe, Taiwan, Tibet), through the derivation of palaeotemperature and palaeopressure information from such rocks, to observational and theoretical studies of regions that are undergoing deformation and metamorphism today. Papers are abstracted separately with the original journal citation. -after Publisher